Analysis of PPH Calculations for Individual Taxpayers According to PP 55 2022 (Case Study Aertembaga District) - Miran, Michael; Evinita, Lenny; Feiby Worang, Tesalonika (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2024)
Income tax is a type of tax that is a source of state revenue. Income tax is a fee charged to individuals, companies, and other legal organizations on the profits they earn. This research aims to determine the criteria and calculations for individual taxpayers who run a business and have a certain gross turnover in accordance with PP 55 of 2022 for businesses in Aertembaga District. The objectives of this research are: 1. To find out whether the analysis of the criteria for individual taxpayers for business owners who have a certain distribution in Aertembaga sub-district is in accordance with PP 55 of 2022? 2. To find out whether the calculation of income tax for individual taxpayers for business owners who have a certain circulation in the Aertembaga sub-district is in accordance with PP 55 of 2022? The benefits of this research are: 1. Theoretical benefits of this research will be able to increase insight regarding individual taxpayers' income tax and gross turnover in accordance with PP 55 of 2022. 2. Practical benefits of this research will be able to provide opportunities for business owners to find out how to calculate income tax in accordance with PP 55 of 2022. The method used in this research is qualitative, the data processed as research material is primary data and secondary data for individual taxpayers in Aertembaga District in 2022. Results research shows that Gracia Restaurant, Jemi Workshop, Yemima Laundry and Feodora Laundry have met the criteria of PP 55 of 2022. The income tax calculation of PP 55 of 2022 is appropriate and can be used by Gracia Restaurant, Jemi Workshop, Yemima Laundry and Feodora Laundry, including income from Jemi Workshop whose income has reached above Rp. 500,000,000 so there is tax that must be paid by Jemi's Workshop.